2021
DOI: 10.1021/acs.energyfuels.1c02703
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performances of ZnO–NiO–CuO Mixed Metal Oxides as Smart Electrode Material for Solid-State Asymmetric Device Fabrication

Abstract: Mixed transition-metal oxides are emerging electrode materials, because of their higher electrochemical performances. In the present work, single-metal oxides, binary-metal oxides, and ternary mixed-metal oxides (MMOs) of zinc oxide (ZnO), nickel oxide (NiO), and copper oxide (CuO) are successfully prepared by simple gel-combustion process. The structure and properties of MMOs are of great interest, because of the opportunity to tune their properties for better multifunctional performance than single and binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…A capacitance retention of 98.3% at a current density of 1.2 mA/cm 3 after 4400 cycles and 99.4% coulombic efficiency during the whole cycle confirm the good cyclic stability of this EESD as an energy storage device with an ultralong lifespan. Importantly, the energy storage ability of devices can be judged by energy density and power density. , The volumetric power/energy densities can be calculated using the following formula: E = prefixtrue∫ t 1 t 2 I V nobreak0em0.25em⁡ normald t = 1 2 C ( V 1 + V 2 ) ( V 2 V 1 ) P = 3600 E t …”
Section: Resultsmentioning
confidence: 99%
“…A capacitance retention of 98.3% at a current density of 1.2 mA/cm 3 after 4400 cycles and 99.4% coulombic efficiency during the whole cycle confirm the good cyclic stability of this EESD as an energy storage device with an ultralong lifespan. Importantly, the energy storage ability of devices can be judged by energy density and power density. , The volumetric power/energy densities can be calculated using the following formula: E = prefixtrue∫ t 1 t 2 I V nobreak0em0.25em⁡ normald t = 1 2 C ( V 1 + V 2 ) ( V 2 V 1 ) P = 3600 E t …”
Section: Resultsmentioning
confidence: 99%
“…CV is a flexible electrochemical method for analyzing redox status, in a variety of mechanical and investigative settings. Its typical applications include drugs performance assessment in pharmaceuticals [36,37], biological samples label measurements and bio-molecules discovery, such as hormones [38,39].…”
Section: Types Of Analytical Electrochemical Techniques For Bs CV Tec...mentioning
confidence: 99%
“…This arises due to the two distinct metal cations having numerous oxidation states that enable charge transfer through the process of hopping. As a result, bimetallic oxides have lower activation energies for electron transfer between cations allowing them to undergo multiple redox processes. , Haratbar et al prepared bimetallic Ni 0.25 Co 0.25 O 4 /electrospinning carbon nanofiber (ECNF) electrode material, which showed better electrochemical activity than the monometallic oxide/etched nitrogen-doped carbon foam (ENCF) electrode. Their study revealed that the better performance is due to two different transition metals with variable oxidation states .…”
Section: Introductionmentioning
confidence: 99%